Progressive web applications as a tool to achieve SDG 4 and SDG 8: Evidence from vocational schools in marginalized regions - Mara, Andry Ananda Putra Tanggu; Surjono, Herman Dwi; Yuniarti, Nurhening (Journal of Education and e-Learning Research, 2026)
Ensuring equitable vocational education in remote areas remains challenging due to limited infrastructure, unstable connectivity, and shortages of qualified teachers. This study examines the implementation of a Progressive Web App (PWA)–based learning ecosystem to enhance learning access, competency development, and employability outcomes in seven vocational schools across Pulau Sumba, one of Indonesia’s least developed regions. A proprietary platform (https://www.pwa-smk.id/) integrating an Academic Information System, e-learning, and internship (Prakerin) management was developed with offline-first caching, low-bandwidth microlearning, and cross-device accessibility. Using an explanatory sequential mixed-methods design, the quantitative phase involved 214 students, followed by qualitative data from 32 purposively selected teachers and school managers, complemented by system-generated engagement logs. Ethical approval was obtained from Universitas Negeri Yogyakarta (No. B/2795/UN34.21.LS.17/LT/2025). The results demonstrate substantial improvements in learning access, vocational and digital skills, and user engagement. Online learning access increased from 46.2% to 87.9%, with 68.1% of materials accessed offline. Pre- and post-assessments showed gains in hard skills (31.1%), soft skills (31.6%), digital literacy (46.7%), and certification readiness (47.0%). The intervention contributed to multiple SDGs, including quality education, youth employability, reduced inequalities, and sustainable practices. Community spillover effects included increased parental involvement, MSME engagement, and digital literacy uptake. Overall, the findings provide strong empirical evidence that context-adapted PWA solutions offer a cost-effective and inclusive approach to accelerating vocational education and community transformation in remote areas.